Root attributes dominate the community assembly of soil fungal functional guilds across arid inland river basin - Wang, Yin; Wang, Jianming; Qu, Mengjun; Li, Jingwen (Frontiers in Microbiology, 2022)
Plant attributes are increasingly acknowledged as key drivers shaping soil fungal communities, but considerable uncertainty exists over fungal community assembly mechanisms and their plant drivers based only on inferences from plant aboveground attributes. To date, empirical evidences of how root attributes are integrated into microbiome–plant linkages remain limited. Using 162 soil samples from a typical arid inland river basin in China, we assessed the drivers that regulate the distribution patterns and assembly processes of total, mycorrhizal, saprotrophic and pathotrophic fungi in surface (0–15 cm) and subsurface soils (15–30 cm). Total fungi and fungal functional guilds exhibited similar distribution patterns in arid inland river basins. Null-model and variance partitioning analysis revealed that the heterogeneous selection induced by root attributes, rather than dispersal limitation, predominated the fungal community assembly. Multiple regressions on matrices further demonstrated that specific root length were the most important predictors of fungal community assembly, which mediated the balance of assembly processes of soil fungal communities. Heterogeneous selection decreased for total, mycorrhizal and saprotrophic fungi, but increased for pathotrophic fungi with increasing specific root length. Additionally, fine-root biomass exerted important effects on fungal assembly processes in subsurface soil but not in surface soil, suggesting root attributes differently affected fungal community assembly between surface and subsurface soil. Collectively, our study highlights the importance of considering root attributes in differentiating the balance of stochastic and deterministic processes in microbial community assembly.